Poéticas do ator no audiovisual: o ator co-criador na produção brasileira contemporânea - Ribeiro, Walmeri Kellen (2010)
Considering the hypothesis that Brazilian audiovisual production presents, as a fundamental element of it"s creative process, the actor as a co-creator of the final audiovisual work, this thesis investigates the creation procedures which are the basis of this actor"s work, such as the unfoldings of this co-creation relation. Using the analysis of creation processes of the films Bicho de Sete Cabeças (Brainstorm), Cidade de Deus (City of god), Lavoura Arcaica (To the Left of the Father), Contra Todos (Up against them all), Céu de Suely (Love for Sale), Crime Delicado (Delicate Crime) and of the miniseries Pedra do Reino and Capitu, and having the Critica de Processo (Process critics), proposed by Cecília Almeida Salles (2006) as a basis, this study sees the creation laboratory as a locus of investigation, experimentation and emergence in audiovisual work, in which the improvisation practice is configured as a procedure to be used in the search of creative and aesthetic possibilities. With this assumption, by proposing a dialog between audiovisual studies (Machado, Burch and Aumont), studies of the actor (Artaud, Grotówski, Stanislávski, Barba and Burnier) and of the contemporary scenic production (Cohen, Zumthor, Fischer-Lichte, Lehmann), we"ll point out some unfoldings and displacements in tradicional cinematographic praxis. As a result of these procedures, a transformation finds its course, in the modes of audiovisual production, approaching those with modes of contemporary scene creation. Aiming the comprehension of the audiovisual object"s meaning regimes own comunication processes, the theoretical reference of this research is established upon theory connections between many knowledge fields, audiovisual theories, actor and scenic creation studies, as mentioned above, the process of creating in a net (Salles), and the theories about corpomídia (or mediabody , by Greiner, Katz), co-creation and complexity (Morin), emergence (Johnson), fluidity and mobility (Bauman)